2019
DOI: 10.1002/sctm.19-0023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effects of Mesenchymal Stromal Cells on Mouse and Human Islet Function

Abstract: Islet transplantation has the potential to cure type 1 diabetes, but current transplantation protocols are not optimal and there is extensive loss of islet β‐cell insulin secretory function during the immediate post‐transplantation period. Studies using experimental models of diabetes have shown that the coculture of islets with mesenchymal stromal cells (MSCs) prior to transplantation improves graft function, but several variables differed among research groups (e.g., type of MSCs used and the treatment condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 47 publications
6
26
1
1
Order By: Relevance
“…The concentrations of glucose used for basal and glucose‐stimulated OCR measurements mirror those used for our standard static islet insulin secretion assays (Figure C). As shown in Figure C, we consistently observe an MSC‐dependent potentiation of GSIS in both mouse and human islets, and using MSCs derived from multiple tissues including adipose, BM, and kidney . We now demonstrate that the MSC‐mediated improvements in islet insulin secretory function are associated with improved islet mitochondrial bioenergetics.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The concentrations of glucose used for basal and glucose‐stimulated OCR measurements mirror those used for our standard static islet insulin secretion assays (Figure C). As shown in Figure C, we consistently observe an MSC‐dependent potentiation of GSIS in both mouse and human islets, and using MSCs derived from multiple tissues including adipose, BM, and kidney . We now demonstrate that the MSC‐mediated improvements in islet insulin secretory function are associated with improved islet mitochondrial bioenergetics.…”
Section: Resultssupporting
confidence: 68%
“…Thus, we demonstrated improved graft curative capacity in streptozotocin‐induced diabetic mice transplanted with islets cocultured with MSCs, whether grafted at the experimental renal subcapsular site or at the clinically preferred intraportal route . We, and others, have also demonstrated that these findings translate to clinically relevant human islets and human MSCs …”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations